2001
DOI: 10.1177/112972980100200309
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pneumothorax as a Complication of Long-Term Central Venous Port Placement in Oncology Patients. An Observational Study

Abstract: Background and purpose.In percutaneous placement of central venous catheters an inadvertent, direct lesion of the lung parenchyma can occur. This is a cause of iatrogenic pneumothorax, whose incidence is approximately 1 to 4%, largely dependent on the experience of the operator, the site of venipuncture and proba-bly the technique employed. Initial treatment currently ranges from observation alone to formal tube-thoracostomy. In an attempt to define the best initial treatment, if any, we reviewed our personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Incorrectly placed tubes for empyemas may delay drainage and result in loculation of the purulent fluid. [10]…”
Section: Identifying Lines and Tubes And Other Devicesmentioning
confidence: 99%
“…Incorrectly placed tubes for empyemas may delay drainage and result in loculation of the purulent fluid. [10]…”
Section: Identifying Lines and Tubes And Other Devicesmentioning
confidence: 99%
“…While common complications such as kinking or dislocation of the catheter, thrombosis, subcutaneous hematoma, and wound infection are observed in both techniques, some specific serious risks are associated only with CC, including ‘pinch off’ phenomena and pneumo- or hematothorax. The latter complications in particular require further invasive treatment, and admission to a hospital is often necessary [ 8 ]. A recent meta-analysis of six randomized controlled trials (RCTs) from 2014 showed a significantly higher primary success rate for CC but with the exclusive risk of pneumothorax occurrence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The median primary success rates given in various retrospective studies and a small number of single-centre, randomised controlled trials range from 71 to 94% for SCD, and from 90 to 99% for PSV [ 2 , 4 - 13 ]. Common complications, such as kinking or dislocation of the catheter, subcutaneous haematoma, wound infection and nerve palsy, are observed with both techniques; however, specific risks are associated only with PSV, including the ‘pinch-off’ phenomenon, pneumothorax and haemothorax, which in most cases requires further treatment and often admission to hospital [ 14 - 16 ]. In the literature, the rate of pneumothorax and haemothorax after PSV is reported to be about 3%, ranging up to 6% in prospective studies [ 14 - 18 ].…”
Section: Introductionmentioning
confidence: 99%